Low-Temperature Carbon Dioxide Gas Sensor Based on Yolk-Shell Ceria Nanospheres - Zito, Cecilia A. [UNESP]; Perfecto, Tarcísio M. [UNESP]; Dippel, Ann-Christin; Volanti, Diogo P. [UNESP]; Koziej, Dorota (American Chemical Society (ACS), 2020)
Monitoring carbon dioxide (CO2) levels is extremely important in a wide range of applications. Although metal oxide-based chemoresistive sensors have emerged as a promising approach for CO2 detection, the development of efficient CO2 sensors at low temperature remains a challenge. Herein, we report a low-temperature hollow nanostructured CeO2-based sensor for CO2 detection. We monitor the changes in the electrical resistance after CO2 pulses in a relative humidity of 70% and show the high performance of the sensor at 100 °C. The yolk-shell nanospheres have not only 2 times higher sensitivity but also significantly increased stability and reversibility, faster response times, and greater CO2 adsorption capacity than commercial ceria nanoparticles. The improvements in the CO2 sensing performance are attributed to hollow and porous structure of the yolk-shell nanoparticles, allowing for enhanced gas diffusion and high specific surface area. We present an easy strategy to enhance the electrical and sensing properties of metal oxides at a low operating temperature that is desirable for practical applications of CO2 sensors.
Keywords: ceria; chemoresistive; CO2 sensing; hollow structure; PDF analysis